The ballerinas : a novel - Kapelke-Dale, Rachel (St. Martin's Press, 2021)
"Dare Me meets Black Swan and Luckiest Girl Alive in a captivating, voice-driven debut novel about a trio of ballerinas who meet as students at the Paris Opera Ballet School. Thirteen years ago, Delphine abandoned her prestigious soloist spot at the Paris Opera Ballet for a new life in St. Petersburg--taking with her a secret that could upend the lives of her best friends, fellow dancers Lindsay and Margaux. Now 36 years old, Delphine has returned to her former home and to the legendary Palais Garnier Opera House, to choreograph the ballet that will kickstart the next phase of her career--and, she hopes, finally make things right with her former friends. But Delphine quickly discovers that things have changed while she's been away...and some secrets can't stay buried forever. Moving between the trio's adolescent years and the present day, Rachel Kapelke-Dale's The Ballerinas explores the complexities of female friendship, the dark drive towards physical perfection in the name of artistic expression, the double-edged sword of ambition and passion, and the sublimated rage that so many women hold inside--all culminating in a twist you won't see coming, with magnetic characters you won't soon forget"--